IMPACT OF RAINFALL EVENTS ON COMPLIANCE OF BIVALVE MOLLUSC, HARVESTED IN SARDINIA, ITALY, FOR ESCHERICHIA COLI - Spanu, Carlo; Mudadu, Alessandro Graziano; Salza, Sara; Piras, Gabriella; Uda, Maria Teresa; Giagnoni, Lucia; Fois, Giuliano; Pereira, Juliano Gonçalves [UNESP]; Pantoja, José Carlos de Figueiredo [UNESP]; Virgilio, Sebastiano; Tiziana, Tedde (My University, 2024)
Rainfall is one of the most important factors of increased levels of Escherichia coli in bivalve molluscs at production stages. Public health control strategies applied by competent authorities rely on microbiological risk assessment, which is based on the evaluation of the sources of faecal contamination in proximity to bivalve molluscs harvesting areas. The monitoring of indicator microorganism, such as E. coli, for the presence of bacterial and viral pathogens is essential for the determination of the sanitary status of production areas. The present study was aimed to investigate the impact of rainfall events, in terms of abundance and time before harvesting on the content of E. coli in bivalve molluscs farmed in Sardinia (Italy). Enumeration of E. coli was performed according to the most probable number (MPN) method (ISO 16649-3) on 1920 bivalve samples collected from 7 regional counties between 2018 and 2020. Precipitation history data were obtained from the local meteorological agency (ARPAS). The cumulative rain (mm) in the 7 days before sampling showed the highest correlation with E. coli content in bivalve molluscs. The likelihood of non-compliant samples for E. coli increased with the increase of total mm of rain poured in the 7 days before sampling. When the total rain was > 300 mm, 80.5% of the samples were not compliant for E. coli with an odds ratio of 23.6. Precipitation data could be a useful tool to interpret anomalous results from official control authorities and to plan harvesting after a rainfall event on a science-based approach.
Keywords: microbiological monitoring; one health; sanitary status; shellfish